An integral GSCM index for assessment of environmental performance in manufacturing companies. Issue 6 (31st May 2019) - Trujillo-Gallego, Mariana; Sarache, William
Abstract : Purpose: From the green supply chain management (GSCM) approach, the purpose of this paper is to propose a green index as a benchmarking tool to assess environmental performance in manufacturing companies. The index involves 10 green practices and 46 performance dimensions, which were identified by way of an exhaustive literature review. Design/methodology/approach: The GSCM index was designed as follows: survey design; experts group selection; relationship identification and green practice weighting (DEMATEL method); and GSCM index construction. The proposed GSCM index was validated at a set of ten Colombian manufacturing companies, which belong to different industrial subsectors. Findings: The structural relationships between both green practices and performance dimensions (cause group vs effect group) were determined. Consequently, a set of green practices and performance dimensions on which managers must focus their environmental efforts (cause group), in order to positively affect the system as a whole, was identified. The environmental performance of a set of manufacturing companies was established. Practical implications: As a decision support tool, the GSCM index provides a baseline for the deployment of environmental improvement plans. It also permits the comparison of environmental performance between companies from different industrial sectors. Further, it can be used to monitor internal operations and collaboration programs in each echelon of the supply chain. Originality/value: This publication contributes to the field of environmental performance measurement by introducing a new index, from the GSCM perspective. In contrast with the existing green indicators, the proposed index is the first to consider causal relationships between green practices and between their performance dimensions.